SDWG Strategic Framework - Part One: Strategic Vision; Part Two: Implementation Plan - Sustainable Development Working Group (SDWG) (Arctic Council Secretariat, 2017)
Building self-sufficient, resilient, and healthy Arctic communities for present and future generations, while protecting the environment and means of subsistence and creating conditions for the preservation and development of cultural traditions, will continue to be a primary goal of the SDWG. Through its work, the SDWG will develop networks that strengthen the capacity of Arctic Indigenous peoples and Arctic communities as a whole. The aim is to provide decision-makers with knowledge-based information, derived from a combination of scientific data, Indigenous peoples' traditional knowledge and local knowledge and to provide this information through outreach and communication channels appropriate for its stakeholders.